2009
DOI: 10.2337/db08-1775
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Link Metabolism and Regulation of the Insulin-Sensitizing Fibroblast Growth Factor-21

Abstract: OBJECTIVEFibroblast growth factor (FGF)-21 improves insulin sensitivity and lipid metabolism in obese or diabetic animal models, while human studies revealed increased FGF-21 levels in obesity and type 2 diabetes. Given that FGF-21 has been suggested to be a peroxisome proliferator–activator receptor (PPAR) α–dependent regulator of fasting metabolism, we hypothesized that free fatty acids (FFAs), natural agonists of PPARα, might modify FGF-21 levels.RESEARCH DESIGN AND METHODSThe effect of fatty acids on FGF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 29 publications
11
124
2
3
Order By: Relevance
“…PPARα activation increases FGF21 levels. FGF21 improves energy production by increasing the utilization of fatty acids (51) and is a potent inhibitor of hepatic steatosis (52). Our results showed that FGF21 levels were elevated in Arv1 -/ -animals.…”
Section: Arv1supporting
confidence: 53%
“…PPARα activation increases FGF21 levels. FGF21 improves energy production by increasing the utilization of fatty acids (51) and is a potent inhibitor of hepatic steatosis (52). Our results showed that FGF21 levels were elevated in Arv1 -/ -animals.…”
Section: Arv1supporting
confidence: 53%
“…* p <0.05, ** p <0.01 and *** p <0.001 vs vehicle-treated groups (indicated as -). Each experiment was repeated three times The increase of FGF-21 plasma concentration by exogenous glucagon regardless of endogenous insulin production is somehow intriguing, in view of the contradictory results of earlier studies showing that insulin regulates FGF-21 [12,15,17,30]. Exogenous insulin increased plasma FGF-21 and Fgf-21 mRNA expression in skeletal muscle in humans [30].…”
Section: Discussionmentioning
confidence: 96%
“…FGF-21 was detectable in four of 14 patients before and 11 of 14 patients after insulin administration. In healthy humans an approximately sevenfold increase in plasma insulin led to an approximately 10% increase in circulating FGF-21 [17]. In contrast, removal of exogenous insulin in humans with type 1 diabetes resulted in an approximately 10% increase in plasma FGF-21 [18], suggesting that insulin reduces FGF-21.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies in different ethnic groups have demonstrated an increased concentration of circulating FGF21 in obese individuals (11 ) and patients with type 2 diabetes (12 ), dyslipidemia (13 ), insulin resistance (14 ), and nonalcoholic fatty liver disease (15,16 ). The increased FGF21 concentrations in obesity are attributable to increases in free fatty acids (FFAs), which can directly stimulate FGF21 expression through the activation of PPAR␣ (17 ). Hyperinsulinemia during glucose clamping studies has been shown to induce FGF21 expression in human skeletal muscle (18 ).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%